Digital Media Management Strategy of the Protocol Division Region Secretariat of Yogyakarta Special Region Through E-Government - Claresta Putri; Fajar Junaedi (Jogjakarta Communication Conference (JCC), 2026)
The use of digital media by the government has become an important part of e-government implementation to enhance information transparency and public communication. However, the management of digital media is not always carried out by units that have a formal public communication function, leading to the emergence of dynamic management practices at the unit level. This research analyzes the practice of managing digital media by local government Protocol units within the framework of e-government through the perspective of institutional role differentiation to understand the division of institutional roles that influence digital media management within government organizations. This research uses a qualitative approach with case study methods, in-depth interviews, and documentation analysis. The research results show differences in the interpretation of e government practices at the unit level. The Protocol Unit in media practice functions more as a means of reporting regional leader activities rather than as a strategic communication medium. These findings indicate that the practice of digital communication within work units is influenced by the division of roles and functions of authority, as well as the work culture of local government bureaucracy. With an institutional perspective, this research emphasizes the importance of understanding the internal dynamics of the bureaucracy in assessing the practice of government digital media management through e-government studies.